Nilai Tambah VCO Pada Unit Bisnis Agroindustri “Andana” di Kabupaten Lombok Utara - Tajidan Tajidan; Halil Halil; Efendy Efendy; FX Edy Fernandez (Jurnal Gema Ngabdi, 2019)
Community service aims to improve understanding and application of financial management in the "Andana" VCO agroindustry business unit, and measuring the performance of its financing. Community service is carried out using the literasi, tutorial and assistance method. Tutorial participants' understanding of financial management is measured from the results of the pre test and post test, while the application of financial management is assessed by financial inclusion, and financing performance is measured using a value added analysis tool. The results of community service activities show that financial management understanding has increased from 77,69 to 81,72 (from good to superior). The application of financial management leads to the application of financial inclusion, while the achievement of value added was IDR 83,200 / liter in June 2019 and IDR 95,681 / liter in July 2019